Disruption of IL-21 signaling affects T cell-B cell interactions and abrogates protective humoral immunity to malaria. - Damián Pérez-Mazliah; Dorothy Hui Lin Ng; Ana Paula Freitas do Rosário; Sarah McLaughlin; Béatris Mastelic-Gavillet; Jan Sodenkamp; Garikai Kushinga; Jean Langhorne (PLoS Pathogens)
Interleukin-21 signaling is important for germinal center B-cell responses, isotype switching and generation of memory B cells. However, a role for IL-21 in antibody-mediated protection against pathogens has not been demonstrated. Here we show that IL-21 is produced by T follicular helper cells and co-expressed with IFN-γ during an erythrocytic-stage malaria infection of Plasmodium chabaudi in mice. Mice deficient either in IL-21 or the IL-21 receptor fail to resolve the chronic phase of P. chabaudi infection and P. yoelii infection resulting in sustained high parasitemias, and are not immune to re-infection. This is associated with abrogated P. chabaudi-specific IgG responses, including memory B cells. Mixed bone marrow chimeric mice, with T cells carrying a targeted disruption of the Il21 gene, or B cells with a targeted disruption of the Il21r gene, demonstrate that IL-21 from T cells signaling through the IL-21 receptor on B cells is necessary to control chronic P. chabaudi infection. Our data uncover a mechanism by which CD4+ T cells and B cells control parasitemia during chronic erythrocytic-stage malaria through a single gene, Il21, and demonstrate the importance of this cytokine in the control of pathogens by humoral immune responses. These data are highly pertinent for designing malaria vaccines requiring long-lasting protective B-cell responses.